Bio-oil Quality Based on Coconut Carbon Biomass Using Pyrolisis Method - Ratnasari, Rifa; Wardhani, Gladys Ayu Paramita Kusumah; Taufiq, Agus (Indonesian Journal of Chemical Research, 2024)
Coconut shells are biomass composed of carbon, hydrogen, oxygen, nitrogen, and other components in small quantities. Biomass can be converted into bio-oil via the pyrolysis method. Bio-oil resulting from pyrolysis has poor quality because it contains oxygen, acid compound, ketone, and ester. To improve the quality of Bio-oil, the pyrolysis process is carried out through a catalytic esterification reaction using a sulfonated H2SO4 coconut shell charcoal catalyst. Bio-oil synthesis is carried out at a temperature of 300–500 ℃. Coconut shell acid catalyst preparation was carried out by activation using HCl and followed by sulfonation of H2SO4 at a temperature of 150℃ for 12 hours. The catalyst was characterized using XRD, FTIR, and SEM. The bio-oil obtained was tested for density, kinematic viscosity, water content, pH, ash content, acid value, Bio-oil composition using GCMS, and metal content using ICP-OES. The results of catalyst characterization show that the formed solid carbon-based catalyst from coconut shells has a graphite crystal structure with a densely porous surface and contains sulfonate functional groups. The yield of bio-oil produced was 6.4%.